Modern Concrete Construction manual : structural design, material properties, sustainability - Peck, Martin, ....- (München : Institut für internationale Architektur-Dokumentation, 2014)
Once an innovative, modern building material, which later fell into disrepute due to some very stereotypical applications in recent times, concrete, with its many different facets, is now more popular than ever among designers and clients. As well as its wide range of static and structural properties, the great diversity of the material's qualities and surface finishes offers enormous potential. In addition to the technical possibilities classically ascribed to concrete construction, the current debate around energy efficiency and sustainability is making it increasingly attractive because it seems ideal for meeting certain requirements. This publication focuses not only on the design and structural planning of concrete structures, but also on its materiality and haptic and sensual side. Exposed concrete with a "flawless smooth grey" finish is not the only quality that concrete has to show for itself. Designers and interior designers are now using concrete to create innovative furniture and spaces of hitherto unimaginable sensuality. The "Modern Concrete Construction Manual" gives planners sound expert information on concrete, from its manufacture and materiality through to designing concrete structures and including the current possibilities of digital design and manufacturing processes. Covering issues such as economic efficiency, energy and sustainability, repairing and restoring concrete structures, and continuing through to design and interior design, this standard reference work offers readers comprehensive knowledge, down to the last detail. An extensive selection of built examples is designed to provide inspiration and encourage designers and planners to put this classic building material to modern use.
Keywords: Betonconstructie -- architectuur